Enhancing Cybersecurity Awareness among University Students: A Study on the Relationship between Knowledge, Attitude, Behavior, and Training - Anwar Fattah; Wagimin Wagimin; Nurlia Nurlia (Jurnal Sistem Informasi, 2023)
The purpose of this research is to explore and measure the level of cybersecurity awareness among university students. Specifically, we aim to examine the relationships between knowledge, attitude, behavior, and training in shaping cybersecurity awareness. By understanding these factors and their interplay, we can identify potential areas of improvement and develop targeted interventions to enhance cybersecurity awareness among university students. The quantitative data analyzed by the smallest partial quadratic structural equation method (PLS-SEM) using Smart PLS 3.0 with 64 respondents from students’ univeristy. The results obtained from this dataset show a positive significant relationship between knowledge; attitude, behavior, and training all have a positive impact on cybersecurity awareness among university students.